1998
DOI: 10.1073/pnas.95.5.2302
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 regulates p53-dependent gene expression

Abstract: Mutations in BRCA1 are present in 45% of families that segregate with susceptibility for breast cancer and in 80-90% of families with both breast and ovarian cancer. Here we report that BRCA1 stimulates artificial and genomic promoter constructs containing p53-responsive elements. This activity of BRCA1 depends on the presence of wild-type p53, which was shown by using mouse fibroblasts expressing temperature-sensitive forms of p53, or p53(؉͞؉) and p53(؊͞؊) fibroblasts obtained from p53 knockout mice. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
285
1
3

Year Published

1999
1999
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 351 publications
(293 citation statements)
references
References 33 publications
(52 reference statements)
4
285
1
3
Order By: Relevance
“…BRCA1 has been shown previously to interact with a number of different proteins, including but not limited to ATF1, p53, Myc, STAT1 and the CBP-interacting protein CtIP (Ouchi et al, 1998(Ouchi et al, , 2000Wang et al, 1998;Yu et al, 1998;Zhang et al, 1998;Houvras et al, 2000). However, in a previous study describing the regulation of the cyclin-dependent kinase inhibitor p27 Kip1 by BRCA1, we determined that none of the already identified partners of BRCA1 were involved with this function (Williamson et al, 2002).…”
Section: Discussionmentioning
confidence: 83%
“…BRCA1 has been shown previously to interact with a number of different proteins, including but not limited to ATF1, p53, Myc, STAT1 and the CBP-interacting protein CtIP (Ouchi et al, 1998(Ouchi et al, , 2000Wang et al, 1998;Yu et al, 1998;Zhang et al, 1998;Houvras et al, 2000). However, in a previous study describing the regulation of the cyclin-dependent kinase inhibitor p27 Kip1 by BRCA1, we determined that none of the already identified partners of BRCA1 were involved with this function (Williamson et al, 2002).…”
Section: Discussionmentioning
confidence: 83%
“…In view of our data demonstrating for the conformation mutant p53D237 ± 239 the loss of and for the DNA contact mutant p53(273H) the defectiveness in recombination inhibition, these helicase interactions could be envisioned to be of functional signi®cance in recombination control. Most interestingly, the hRad51 complex partner BRCA1 interacts with p53 between amino acids 300 ± 393 (Ouchi et al, 1998;Zhang et al, 1998). BRCA1 can be imagined to stabilize functional interactions between p53 and hRad51.…”
Section: Discussionmentioning
confidence: 99%
“…Homologous recombination appears to be essential during the normal development of mammalian organisms, as can be deducted from the embryonic lethal phenotype of both rad51 nullizygotes (Lim and Hasty, 1996;Tsuzuki et al, 1996), and of BRCA17/7 mice, lacking the tumor suppressor BRCA1 (Hakem et al, 1997;Ludwig et al, 1997), a complex partner of Rad51 (Scully et al, 1997). Survival of the embryos in both knockouts can be prolonged by concomitant knockout of p53, indicating genetic interactions between p53 and Rad51, as well as between p53 and BRCA1 in addition to physical interactions described before (StuÈ rzbecher et al, 1996;Ouchi et al, 1998;Zhang et al, 1998). Previous work has demonstrated that p53 inhibits homologous DNA exchanges in mitotically growing cells (WiesmuÈ ller et al, 1996;Bertrand et al, 1997;Mekeel et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…It remains to be established, whether p53 upon encountering mismatches in heteroduplices transmits signals to downstream molecules, such as p21 waf1 , or/and blocks the progress of DNA exchange, possibly even by participating in error removal through its 3'-45' exonuclease activity. First indications for a p53-mediated signal transduction mechanism coupled to recombination processes can be derived from the fact that the hRad51-complex partners Brca1 and Brca2 physically and genetically interact with p53 (StuÈ rzbecher et al, 1996;Ouchi et al, 1998;Zhang et al, 1998;Lim and Hasty, 1996;Hakem et al, 1997;Ludwig et al, 1997), and that Brca1 seems to stimulate p53-dependent transcription, whereas overexpressed Brca2 and hRad51 display antagonistic e ects (Marmorstein et al, 1998). In line with this proposal is the observation that puri®ed multiprotein complexes performing homologous recombination in vitro contain DNA polymerase e, DNA ligase and low levels of 5'-43' and 3'-45' exonuclease activities (Jessberger et al, 1993).…”
Section: Inhibition Of P53 Recombination Control By Sv40mentioning
confidence: 99%